(3SdWI GdGOYGA GdYGe aj GdJUQa aj GdGSJOdGd hGdJMbjb (B: s (3OQGSI ebGQfI (B/ s - (3Ydj aVd GdHhYjfjfs; (3CMeO YhV HdGds; (3eOMJ QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2001)
(3JfGhdJ GdQSGdI SdWI GdGOYGA GdYGe aj GdJUQa aj GdGSJOdGd hGdJMbjb, MjK HMKfG aj GdLgGJ GdefGW HgG SdWJj GdJMbjb GdGHJOGFj hGdGJgGe(B. (3hbefG HJCUjd gPg GdGfXeI, hJYQVfG ddCfXeI GdebGQfI aj gPG GdeLGd, hHMKfG aj SdWI GdfjGHI aj EUOGQ GdCeQ HMaX GdChQGb hGdPj YQafGg HEfg bQGQ EOGQj jUOQ ef GdfjGHI HfGA Ydi eMGVQ GdGSJOdGd JYOd HehLHg Yf JhLjg GdGJgGe(B. (3hHjfG CSHGH gPG GdCeQ hBKGQg GdbGfhfjI(B. (3Ke JWQbfG Edi GdEJLGg GdeYGQV dgPG GdGJLGg hGHQRfG OYGFeg hYjhHg(B. (3Ke JMOKfG Yf JUQa GdfjGHI aj GdJMbjb, MjK YQafG GdCeQ HChdGLg GdEbGeI GdOYhi HEfg CeQ bVGFj jUOQ ef GdfjGHI GdYGeI JbQQ HebJVGg YOe GdSjQ aj GdOYhi hHjfG BKGQg GdbGfhfjI(B. (3hGNjQkG JWQbfG Edi GdCeQ HGdEMGdI hYQafGg HCfg bQGQ jUOQ ef GdfjGHI Hfbd GdOYhi GdLRGFjI ef eQMdI GdJMbjb GdEHJOGFj Edi eQMdI GdeMGceI, hJYQVfG dGfhGY GdEMGdI aj GdfXGejf GdCfLdh CeQjcj hGdGJgGej, eY HjGf CfhGY GdEMGdI hCKQgG GdbGfhfj aj Ohd GdNdjL GdYQHjIs
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj (B2001.s
(3HHdjhLQGajG(B: (3UaMGJ (B425-438.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3GdGSJOdGd hGdJMbjbs; (3GdJUQas; (3SdWI GdEOYGA GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs